2022
DOI: 10.3390/ijms23084408
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Anti-Angiogenic Effect of Combined VEGFR Kinase Inhibitors, Lenvatinib, and Regorafenib: A Therapeutic Potential for Breast Cancer

Abstract: Background: Breast cancer currently affects more than two million women worldwide, and its incidence is steadily increasing. One of the most essential factors of invasion and metastasis of breast cancer cells is angiogenesis and non-angiogenic vascularization. Lenvatinib and Regorafenib share the same anti-angiogenic effect by inhibiting vascular endothelial growth factor receptors (VEGFRs subtypes 1 to 3) and have been approved for treating different types of cancer. Methods: We investigated Lenvatinib and Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Biological‐based models are available for the analysis and prediction of DDIs in the study of lenvatinib. In a study evaluating the therapeutic efficacy of lenvatinib in combination with regorafenib for breast cancer, it was shown that the combined administration of these drugs exhibited a synergistic effect on the survival of breast cancer cells, with observed variations in drug concentration 23 . Furthermore, the combination of lenvatinib and erlotibib, both VEGRF inhibitors, has been found to enhance the treatment of HCC by overcoming drug resistance 24 …”
Section: Discussionmentioning
confidence: 99%
“…Biological‐based models are available for the analysis and prediction of DDIs in the study of lenvatinib. In a study evaluating the therapeutic efficacy of lenvatinib in combination with regorafenib for breast cancer, it was shown that the combined administration of these drugs exhibited a synergistic effect on the survival of breast cancer cells, with observed variations in drug concentration 23 . Furthermore, the combination of lenvatinib and erlotibib, both VEGRF inhibitors, has been found to enhance the treatment of HCC by overcoming drug resistance 24 …”
Section: Discussionmentioning
confidence: 99%
“…A clinical trial was conducted using PD-L1 with a multi kinase inhibitor in patients with MSS or pMMR CRC. Regorafenib targets stromal and oncogenic receptor tyrosine kinases, and shows anti-angiogenic activity due to its dual-target VEGFR2-TIE2 tyrosine kinase inhibition[ 143 ]. The NCT04126733 trial conducted between 2019 and 2022 included 94 CRC patients with MSS or pMMR[ 144 ].…”
Section: Clinical Trials Involving Checkpoint Inhibitors In Crcmentioning
confidence: 99%
“…Due to its insidious pathogenesis, approximately 70-80% of patients have developed late stages upon diagnosis, requiring targeted therapy [2][3][4]. Lenvatinib is one of the multi-target tyrosine kinase inhibitors (TKIs) targeting a collection of receptors primarily affecting angiogenesis [5,6]. Despite the notable survival benefits of lenvatinib in advanced HCC patients, lenvatinib resistance (LR) occurs throughout the entire process of targeted therapy and significantly compromises the prognosis of HCC patients [7].…”
Section: Introductionmentioning
confidence: 99%